THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ON STUDENT’S LEARNING OUTCOMES AND STUDENT’S ACTIVITY - Yeni Sipangkar; Rita Juliani; Andil Siregar (Universitas Negeri Medan, 2018)
The objective of study to determine the effect of Guided Inquiry learning models to student learning outcomes and student’s activity in dynamic electrical topic. This type of research is quasi-experimental design of the Pretest-Posttest Design Control Group. The research was conducted at SMA Swasta Katolik Budi Murni 3 Medan in A.Y 2017/2018. The population of research was all students of class X. Sampling is done by random sampling by taking two classes randomly, namely class X-A as the control class and class X-B as the experiment class. The instrument used in the study was a test of learning outcomes and an observation sheet of student learning activities. Learning outcomes test in the form of a test essay with a number of 15 questions and before using the question validated by the validator. The study was conducted by giving measurements in the form of a pretest and then given treatment with a guided inquiry learning model and within a certain period of time and then given a posttest. The results of data analysis using the t test of one party shows that there are differences due to the influence of the guided inquiry learning model on student learning outcomes in Dynamic Electrical material. Keywords: Guided Inquiry Learning Model, Learning Outcomes, Learning Activities